Improved analysis of TCR[gamma][delta] variable region expression in humans - Christopoulos, Petros (Journal of immunological methods, 2016)
Deeper understanding of γδ Τ cell increases in various clinical situations requires the assessment of TCRγ and δ variable (V) region gene expression and junctional diversity. Here we describe an improved TCRγ and δ spectratyping method used to study the γδ T-cell expansions in two patients with thymoma and immunodeficiency. One of these patients also suffered from chronic CMV infection and pure red cell aplasia and the other from chronic visceral leishmaniasis and myasthenia gravis. Analyses of the junctional diversity of the TCRγ and δ chains, flow cytometry with a panel of non-commercially available anti-TCRγδ V region monoclonal antibodies and functional studies were performed. The results clearly distinguished an expansion of oligoclonal, most likely antigen-driven, cytotoxic γδ T cells in the first patient from a naive pattern of polyclonal γδ T-cell proliferation in the second. These findings demonstrate the diversity of γδ T-cell expansions in immunodeficient patients and highlight the value of spectratyping as a tool for their characterization and understanding of the underlying mechanisms.